Inhabiting the sinkhole?: Urban mining and environmental social mobilization in Soacha - Medellín-Pérez, Iris Alejandra (Sociedad y Economía, 2022)
This article deals with two cases of urban communities neighboring mining projects in the municipality of Soacha and its main objective is to understand how mobilization against mining arises in these communities. For this reason, the situation in which the mobilization exercise is carried out is compared with the situation in which the mobilization exercise is not carried out. All these cases are adjacent to the mining area of the city, have a similar socioeconomic composition, and use information obtained from documents and interviews to analyze the timeliness of the two using qualitative comparison methods. Two factors have been found to explain the emergence of mobilization: On the one hand, the existence of an administration that constitutes political opportunities that are perceived as such. On the other hand, the appropriation of institutionalized organizational space plus organizational alliances.